2015
DOI: 10.1007/s13762-015-0815-0
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the use of cactus Opuntia ficus indica in the biocoagulation–flocculation of Pb(II) ions from wastewaters

Abstract: Coagulation-flocculation processes play an important role in the treatment of water using inorganic and synthetic materials. Presently, cactus Opuntia ficus indica is explored as a cheap, abundant and eco-friendly bioflocculant of Pb(II) ions from aqueous solutions. The cactus powder was characterized by Fourier transform infrared spectrometer (FTIR), and the coagulation-flocculation process was optimized for pH, initial concentration of Pb(II) ions, particle size, dosage, ionic strength, contact time and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 22 publications
2
24
0
5
Order By: Relevance
“…A study reported by Aweng E.R. et al [13] proved that Cassia alata or also known as Senna alata as natural coagulant able to reduce river water turbidity up to 93.33%. Further testing on SA, shows that it has significant antimicrobial effect against Gram positive bacteria and fungi.…”
Section: Senna Alatamentioning
confidence: 99%
“…A study reported by Aweng E.R. et al [13] proved that Cassia alata or also known as Senna alata as natural coagulant able to reduce river water turbidity up to 93.33%. Further testing on SA, shows that it has significant antimicrobial effect against Gram positive bacteria and fungi.…”
Section: Senna Alatamentioning
confidence: 99%
“…Other studies have reported that the application of natural coagulants can increase the concentration of orthophosphate, nitrogen compounds (nitrite and nitrate) and organic matter [27,32]. This is mainly due to the functional groups present in cacti, i.e., amide, amine and amino acids [30,35] and Opuntia mucilage, which show high concentrations of metals in their compositions [8].…”
Section: Physical-chemical Removal Profilementioning
confidence: 99%
“…The bio-coagulation mechanisms of cacti were reported as adsorption-charge neutralization and adsorptionbridging mainly due to the anionic and macromolecular nature of deprotonated polygalacturonic acid [25,30]. Considering all removal characteristics, studies have reported that cacti present removal rates similar to those obtained using chemical coagulants, with the advantage of generating biodegradable sludge [37].…”
Section: Physical-chemical Removal Profilementioning
confidence: 99%
“…To combine the best properties of both types, it was suggested that synthetic PEs be grafted onto the backbone of natural polymers. A completely natural PE has been obtained from the cactus tree (Opuntia ficus-indica) [62,63]. Others have been reviewed [4].…”
Section: New Polyelectrolytesmentioning
confidence: 99%